Scholarly research in music : shared and disciplinary-specific practices - Lee, Sang-Hie (New York : Routledge, 2022)
"Scholarly Research in Music: Shared and Disciplinary-Specific Practices, Second Edition offers a comprehensive and detailed guide to engaging in research in all disciplines of music. This second edition continues to provide the foundational principles of research for all musicians, including performers, theorists, composers, conductors, music educators, and musicologists. It strengthens the core pedagogical framework of the first edition by offering updated guidance on available technologies, methodologies, and materials. Driven by the rapidly shifting research paradigms within music, sixteen contributors expand the already broad scope of the book, with new chapters on research in today's library, neurophenomenology in music, and self-efficacy in music performance, as well as new sections in chapters on philosophy, historical research, social science research, and statistics. Introducing research as a friendly and accessible process, the book engages students in brainstorming a topic, asking pertinent questions, systematically collecting relevant information, analyzing and synthesizing the information, and designing a cohesive research plan to conduct original research. Detailing the methodologies and techniques of both conventional and innovative approaches to music research, Scholarly Research in Music provides an essential grounding for all kinds of music researchers"--
Keywords: Musicology; MUSIC / General; MUSIC / Ethnomusicology